Are Dealers Still Relevant? How Dealer Service Quality Impacts Manufacturer Success. Issue 10 (9th June 2021) - Golara, Sina; Dooley, Kevin J.; Mousavi, Nasim
Abstract : Most automobile manufacturers use franchised dealers to distribute their products and to perform sales‐related and after‐sales services. However, the link between dealers' service quality and manufacturer performance is not well understood. Some studies suggest that these services' quality affects product sales, repeat sales, and brand reputation. Others posit that dealer services are a commodity, and their quality may only affect sales in the extremes. We constructed data representing sales and service quality ratings of 1078 U.S. automobile dealerships over a year in five different car classes. We find that the quality of after‐sales services positively influences sales of the brand in the dealer's region. Manufacturers whose dealers struggle with after‐sales services take a hit in market share even in markets where they enjoy superior competitive status. We also find that sales‐related services gain importance in highly competitive markets where the manufacturer has few dealers and competitors have many.